Study of structural relaxation of Ge-Se and Ge-S chalcogenide glasses - Pustková, Pavla; Málek, Jiří; Svoboda, Roman; Čičmanec, Pavel (Univerzita Pardubice, 2006)
The structural relaxation of chalcogenide glasses related to the viscosity behaviour of their undercooled liquids was studied. Both volume and enthalpy relaxation were studied under isothermal and nonisothermal conditions. It was found that the equilibrium time scale of relaxation experiments are practically the same for both volume and enthalpy relaxation. Relaxation behaviour of studied chalcogenide glasses was described by Tool-Narayanaswamy-Moynihan model and the parameters of this model were determined. The volume and enthalpy relaxation can be sufficiently well predicted by using the same set of TNM parameters. The effective activation energy of TNM model is close to the activation energy of viscous flow of undercooled liguid.
Keywords: Chalkogenidová skla; struktura skel; Ge-S system; Ge-Se